(untitled) (Universal International Scientific Journal, 2026)
This article analyzes pedagogical and psychological approaches to teaching a foreign language at the primary education stage. The age characteristics of primary school students, their level of psychological development, and methods for increasing their interest in learning a language are considered. The importance of modern pedagogical technologies, communicative methods, game-based teaching methods, and the formation of motivation in teaching a foreign language is also highlighted.